An Empirical Study on the Influencing Factors of the Returning Intention of Overseas Talents - Liu Liu; Fan Tian (Discrete Dynamics in Nature and Society)
Many scholars have carried out a large number of studies on the factors influencing the intention of returning overseas talents based on different theories. This study integrates two theoretical perspectives at macro and individual levels, puts forward a new theoretical framework for analyzing the intention of returning overseas talents, and constructs a theoretical model including the intention of returning overseas talents, talent ecological environment of the host country, prospect expectation of home country, talent growth expectation, and perceived opportunity. Based on 302 survey samples, we used correlation analysis, confirmatory factor analysis, structural equation, and other methods, and the results show that four variables, including talent ecological environment of the host country, prospect expectation of home country, talent growth expectation, and perceived opportunity, have a significant impact on the intention of returning overseas talents. The research also found that talent growth expectation and perceived opportunity had mediating effects, and the prospect expectation and perceived opportunity of origin had moderating effects, which provides a new research idea for the research on the factors influencing the return intention of overseas talents.